PENGARUH PIJAT BAYI TERHADAP KUALITAS TIDUR BAYI USIA 0-6 BULAN DI POLIKLINIK ANAK RUMAH SAKIT UMUM BANGLI - meita (JURNAL KESEHATAN ALMUSLIM, 2022)
Sleeping quality is a person's satisfaction of sleeping. Sleeping quality affects the baby both physiologically and individual psychology. Good sleeping quality of babies can be identified from the characteristics of falling asleep easily at night, fit when they wake up, not fussy, and do not need naps that exceed their needs according to their development. One way that can be done to maintain the sleeping quality of baby is by applying baby massage. The purpose of this study was to determine the effect of baby massage on the sleeping quality of infants aged 0-6 months. This study used a pre-experimental design with one group pretest-posttest design. The research sample was 49 infants aged 0-6 months taken by purposive sampling. Data analysis used the Wilcoxon Sign Rank Test statistical test. There was a difference in the sleeping quality of infants aged 0-6 months before and after baby massage. The results of the study before applying baby massage was categorized lack sleeping quality of 67.3%. After doing baby massage, it was found that all respondents had good sleeping quality 100% with a p-value of 0.000 where p-value < (0.05) which means that baby massage significantly affected the infants sleeping quality. Keywords: Baby Massage, Sleeping Quality of Infants Aged 0-6 months